Placental alterations and their annexes in fetal deaths. Dr. Gustavo Aldereguía Lima Hospital. 2021-2023 - Niuvys Valera Rodríguez; Caridad Socorro Castro; Javier Martínez Navarro; Lisanka Fumero Roldan; Jorge Enrique Rodríguez León (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Foundation: the human placenta is a mystery. The anatomopathological diagnosis becomes important in the search for factors that can be worked on to avoid fetal deaths. Objective: to determine the macroscopic and microscopic alterations of the placenta and its annexes in specimens from fetal deaths. Methods: a descriptive, retrospective and cross-sectional study was carried out at the Dr. Gustavo Aldereguía Lima Hospital, in Cienfuegos, from 2021 to 2023. 58 placentas and their annexes, received in the Pathological Anatomy Department, were analyzed. Macroscopic and microscopic alterations of the placenta were studied. Results: abnormally small placentas and cords were more represented (24.14 % and 63.79 % respectively); marginal cord insertion (36.21 %), ruptures, twists (8.62 %), cysts (6.90 %), edema (77.59 %), fibrinoid necrosis (72.41 %), immature villi, villitis (43.10 %), excessive number of syncytial knots (3.48 %), fibromuscular sclerosis (20.69 %), the presence of fibrin (82.76%), funisitis (29.31 %), fibromuscular sclerosis (20.69 %) and chorioamnionitis (31.03 %). Conclusions: the results showed a predominance of microscopic alterations, such as fibrin, fibrinoid necrosis and edema. Taking these factors into account, the necessary measures can be taken to avoid fetal death.